Dynamic equivalence to English translation of retroflex suffixation words in Beijing dialect : a case study of Lao She’s Luotuo Xiangzi - Feng, Yajun (2019)
The use of retroflex suffixation words is a representative language phenomenon in Beijing dialect. Apart from the basic semantic meaning contained in each retroflex suffixation word, rhetoric features and cultural connotations also can be found in some of them. What’s more, the position of retroflex suffixation word in sentence is flexible and the grammatical functions played by retroflex suffixation words are varied in different contexts. All of these set challenges to the translation of retroflex suffixation words from Chinese to English. This dissertation aims to examine the translation strategies of the retroflex suffixation words based on the novel Luotuo Xiangzi written by Lao She and its two English versions translated by Shi Xiaojing and Howard Goldblatt. To conduct detailed analysis, the retroflex suffixation words were categorized according to their semantic meanings and expressive functions in the source text. It was shown that there was no fixed or consistent method in the translation of retroflex suffixation words. Methods such as reduction, omission and adaptation were used accordingly in order to achieve similar effects as in the source text. Apart from the need of clear textual expression, the use of dynamic equivalent strategy was also influenced by many underlying causes, such as politics, culture, ideology and translators’ background.